Desenvolvimento de núcleos de Apis mellifera alimentados com suplemento aminoácido vitamínico, Promotor L - Castagnino, Guido Laércio [UNESP]; Arboitte, Miguelangelo Ziegler; Lengler, Silvio; Garcia, Gerson Garcez; Glasenapp de Menezes, Luiz Fernando (FapUNIFESP (SciELO), 2006)
The development in the area of creates was studied of 14 nuclei with four mass off cells from the division of nine beehives of africanized Apis mellifera honeybees, distributed in two treatments: TPL - nuclei fed with inverted sugar + 3.5ml of the vitaminic amino acid supplement (Promotor L® ), composition for six nuclei and TAI - nuclei fed with composed inverted sugar for eight nuclei. The nuclei had been fed weekly in individual feeder's type tray, and the evaluations carried through in four periods, totalizing 74 days. The treatments had not presented significant difference, being that, number the TPL presented area of creates inferior to TAI (233.63 versus. 273.02cm 2, respectively). How much to the periods the four was superior (P<0.05) to the first and as second, being that the third did not present significant difference (P<0.05) in relation to the others. The use of the TAI was economically more favorable in relation to the TPL in R$0.21 in relation to the cost for production of 1kg of food.
Development of nuclei Apis mellifera fed with the vitaminic amino acid supplement Promotor L
Keywords: Area of create; Artificial feeding; Beekeeping; Economic; Inverted sugar; Apis mellifera